Nepravilni trofoblastni vdor v patogenezi preeklampsije - Golob, Nena (Medicinski razgledi, 2010)
The following article describes the relationship between the endometrium, mother's vascular system and the invasive trophobIast. This relationship is crucial for the adaptatioh of the uterus and the placenta during gestation. The article also focuses on the differentiation of the trophobIast, which is composed of cytotrophoblast, syncytiotrophoblast and three developmental formsof cytotrophoblast; the latter is also called the intermediate trophobIast, because based on differentiation it is situated between the cytotrophoblast and the syncytiotrophobIast. One of the forms of the invasive cytotrophoblast, the intermediate invasive trophobIast, plays an important role in the enhancement of uteroplacental blood flow during gestation. It actually remodels mothers' spiral arteries, providing in so doing a higher influx of bloodstream into them. To ensure a healthy pregnancy, the invasion of the intermediate trophobIast into the endometrial stroma has to be well regulated. 1mbalances during the invasion of the trophobIast and the process of decidualization result in the complications of pregnancy. The author particularly focuses on problems related to the ethipatogenesis of preeclampsia and gestational trophoblastic disease.
Keywords: human pregnancy; nosečnost; placenta; preeklampsija; trofoblasti; diferenciacija